Diálogos entre o verbal e o não verbal: um olhar bakhtiniano sobre as manifestações dos tons emotivo-volitivos em filmes publicitários sobre preservação ambiental - Oliveira, Leonardo de (2021)
Expression of the subjects' uniqueness, the tone is an aspect that permeates and delineates all enunciation. In the discursive dynamics, the tone is closely linked to the representations that an enunciator has about his social audience and his saying, which presupposes the attribution of a given socio-hierarchical weight, that is, of an emotionally-volitively motivated valuation, to the (s) your interlocutor (s). Based on these representations of the other and, also, the enunciative situation, the socio-historical context and the sharing of knowledge (known or presupposed) between the subjects involved, the enunciator assumes this or that emotional-volitional tone in the utterances he utters, formatting, thus, its thematic contents, its compositional constructions and its styles. However, the Bakhtin Circle has a broader conception of utterance, comprising as such any coherent set of shared signs that can be understood by a collectivity. Thus assimilated, the Circle's considerations regarding utterances contemplate the fact that they also manifest themselves in support of signs of a nature different from that of the linguistic sign, which is why we assume the premise that, once inherent in any utterance, the tones permeate not only verbal language, but any sign materiality through which utterances come to fruition. In addition to these ideas, Paula and Serni (2017), when investigating the extraverbal potentialities of the utterances, bring to their study the concept of verbivocovisuality, with which they give account of their integrated sound and visual dimensions and which we will use in this work. Considering this expanded vision of the utterances, this research intends to demonstrate how emotive-volitional tones determine the choice and arrangement of the different semiosis that make up integrated advertising films dedicated to environmental preservation. Still thinking about the influence that socio-ideological factors have on the enunciative processes and, consequently, on the tones they assume, we selected three advertising films from different social spheres and with divergent projects todemonstrate the impact of these factors more clearly on their respective and distinct emotive-volitional tones. To this end, we selected an institutional film from the Ministry of the Environment, another one promoted by the Unilever conglomerate and a third initiative by the non-governmental organization SOS Mata Atlântica. The work contributed to shed light on the concept of emotive-volitional tone and, mainly, on its founding role in the enunciative constitution / concretization. Bearing in mind that the concept is still little explored, especially regarding utterances that expressly congregate various semiosis, the focus on the tone through the verbivocovisuality bias undertaken in this research also brought contributions to the understanding of these multisemiotic enunciative processes, allowing us to demonstrate how much the enunciative concretization of the semiosis that it congregates depends on a social soil so that it can be processed.